ENT 530 Social Media Portfolio: Carya Cosmetics / Nazatul Najihah Azman - Azman, Nazatul Najihah (2021)
Carya Cosmetics is an online business that focuses on selling cosmetic products. The product name is Carya Cosmetics. The specialty of the Carya Cosmetics brand is that I am focusing and suggesting a good product that can be used by all people especially woman out there. Carya Cosmetics have so many kinds of makeup set that suitable in certain age. Carya Cosmetics aims to make every girl more confident and beautiful. The management of Carya Cosmetics, I am the one who handles everything in terms of managing my Facebook Page to promote and attract customers. So far, I had purchase four sets of makeup sets. The first time I became a business person who has no experience in terms of entrepreneurship. Nevertheless, as an entrepreneur, I still put on efforts to make my business run smoothly and let the people satisfied with the cosmetic product. Carya Cosmetics products can be said as an expensive product as it is designed by maintaining the quality. People nowadays have much commitment in their lives, making them not interested in trying and buying Carya Cosmetics products. In that case, I had chosen Carya Cosmetics brand as my selected product. Since I had sells it online, I can interact with other people and my potential customer about their makeup problems. This report provides the promotional of the product on social media to introduce the product and the brands of Carya Cosmetics, starting with creating the Facebook page, the URL of the page, the teaser, soft sell, and hard sell. I need to make some plans and come out with many ideas to promote the product. Create something that can attract and fulfill customer satisfaction throughout Malaysia.